2019
DOI: 10.1186/s13244-019-0763-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic stenting of malignant, benign and iatrogenic colorectal disorders: a primer for radiologists

Abstract: In recent years, endoscopic placement of intraluminal stents is increasingly used to manage a widening range of colorectal disorders. Self-expanding metal stents represent an established alternative to surgery for the palliation of unresectable carcinomas and currently allow a “bridge-to-surgery” strategy to relieve large bowel obstruction and optimise the patients’ clinical conditions before elective oncologic resection. Additionally, intraluminal stents represent an appealing option to manage obstructing ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
(65 reference statements)
0
11
0
1
Order By: Relevance
“…Atherosclerosis, thrombosis and lumen stenosis were caused by direct suture of the carotid artery incision. [16][17][18] Cur is a plant polyphenol with a wide range of biological activities. Extensive investigations have shown that Cur exhibits antiproliferative, antimigratory, antioxidant and antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis, thrombosis and lumen stenosis were caused by direct suture of the carotid artery incision. [16][17][18] Cur is a plant polyphenol with a wide range of biological activities. Extensive investigations have shown that Cur exhibits antiproliferative, antimigratory, antioxidant and antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…However severe adverse events only occur in < 5% of procedures[ 10 ]. Stents could be covered or uncovered, with covered stents having a lower obstruction rate[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…SEMS can be covered and uncovered. The uncovered SEMS can be divided into through-the-scope and non-through-the-scope[ 27 ]. The through-the-scope SEMS is inserted through a guidewire.…”
Section: Endoscopic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Данная методика позволила сократить время пребывания больных в стационаре, процент осложнений и необходимость в наложении стомы. [4][5][6] В отличие от опухолевых, в эндоскопическом лечении доброкачественных стриктур, в частности, стриктур анастомозов, методом выбора является бужирование или баллонная дилатация. Одним из важных преимуществ последней является то, что сила, воздействующая на стриктуру, имеет исключительно центробежное направление, тогда как при бужировании сила направлена также по продольной оси.…”
Section: дискуссияunclassified